Association between Prognostic Nutritional Index and Contrast-Associated Acute Kidney Injury in Patients Complicated with Chronic Kidney Disease and Coronary Artery Disease - Xiaoli Dong; Bo Wang; Shiqun Chen; Jin Liu; Yu Xia; Shouhong Wang; Bin Li; Sheng Wang; Ming Ying; Huanqiang Li; Ziling Mai; Yongquan Yang; et al. (Journal of Interventional Cardiology)
Background. Contrast-associated acute kidney injury (CA-AKI) is a major adverse effect of coronary angiography (CAG). Patients with chronic kidney disease (CKD) and coronary artery disease (CAD) are at high risk of CA-AKI. This study aimed to investigate the association between prognostic nutritional index (PNI) and CA-AKI in this high-risk population. Methods. This study enrolled a total of 4,391 patients. CA-AKI was defined as a serum creatinine increase ≥0.3 mg/dL or 50% from baseline within the first 48 hours following CAG. The PNI was calculated upon hospital admission: serum albumin (g/L) + 5 × total lymphocyte count (109/L). PNI was analysed from the high level to low level as a continuous variable and categorical variable which was divided into four groups by quartile. Restricted cubic splines and logistic regression were applied. Results. Overall, 13.09% (575/4391) of patients developed CA-AKI. PNI score was significantly lower in patients with CA-AKI than that in patients without CA-AKI (P<0.01). The relationship between PNI score and CA-AKI was linear. A logistic regression model revealed that decreased PNI score was associated with increased risk of CA-AKI [per 1-point decrement; adjusted OR = 1.08, 95% CI, 1.05–1.09; compared with Quartile 1 (PNI ≥ 46.30), Quartile 4 (PNI < 37.90), adjusted OR = 1.88, 95% CI: 1.41–2.51; and Quartile 3 (37.90 ≤ PNI < 42.15), adjusted OR = 1.37, 95% CI: 1.02–1.84]. Conclusion. Our study indicated a negative linear relationship between PNI score and CA-AKI in patients undergoing CAG complicated with CKD and CAD. It suggested that malnutrition is associated with increased risk of CA-AKI in this population.